EFFICIENCY OF SYNBIOTIC AS FEED ADDITIVES ON GROWTH PERFORMANCE, SURVIVAL RATE AND HEALTH STATUS IN COMMON CARP CHALLENGED WITH SAPROLEGNIA SPP. - Al- Hassani, S. T.; Mustafa , S. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was conducted to investigate the effects of Synbiotic (combination of probiotic and prebiotic) as feed additive on growth performance, survival rate and immune response against Saprolegnia spp. in common carp. A total of 100 C. carpio fingerlings, weighing 49.55–50.50 g were randomly distributed into five treatment groups in duplicate, fishes were fed with different concentrations as follows: (T1) 0.5 %, (T2)1.0 % ,(T3) 1.5 % and (T4 ) 2% as well as the control group were fed basal diet without any addition of synbiotic. Results showed significant increase (P< 0.05) in all growth parameters (i.e. final weight, DWG, RGR, SGR (%), FCR, FCE) compared with the control group. The highest values were observed in fish fed on the diet containing 2% and 1.5% synbiotic. Also, survival rate recorded highest value (100%) in treatment supplemented with synbiotic 2% compared with control group (75%), suggesting that the high level (2%) improve growth rate and survival rate. At the end of experimental period six fish were randomly selected from each treatment and control (C) + for challenge test in a viable fungal suspension (1×105 live zoospores/ml) of Saprolegnia spp. Considerable changes have been observed in the mean values of WBCs. Respiratory burst activity showed significant increased in all synbiotic diet compared to C+ group. These results can be considered as a beneficial dietary for improving the growth rate and immune response in common carp.